Performance measurement system for higher education based on balanced scorecard framework - Kozanoğlu, Orkun. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2002., 2002)
In this study, the Excellence Model of European Foundation for Quality Management (EFQM) has been restructured for higher education institutions and integrated with Balanced Scorecard (BSC) management system and ABET (Accreditation Board for Engineering and Technology) 2000 Model to develop a quality model for engineering schools. The proposed model in this study has three main components, namely, support processes, core processes, and resources. These main components are surrounded by "integrity" concept which represents the culture and values of the institution. The model is driven by the mission and vision of the institution; and feedback for all processes of an engineering school is collected at the ccresults"c omponent. The role of BSC management system in the proposed model is to deploy the vision and strategic objectives of the institution and provide a concrete structure for clarifying faculty members' and administrative staffs' accountabilities. This is performed through the generic strategy map for academic departments which reveals the cause-and-effect relationships between strategic objectives. This study also proposes a departmental scorecard that involves a list of generic performance measures which serve as an input for ccresults" component of the proposed model. By using this generic departmental scorecard, faculty scorecards may be constructed. ABET 2000 evaluates only the engineering programs with its less prescriptive nature compared with the previous ABET model. Thus, with the help of Quality Function Deployment approach, ABET 2000 has been used in the proposed model for deploying the program outcomes into the course learning objectives, modes of delivery and assessment methods. After developing a quality model; analysis of historical information, and information gathered by two surveys performed in Bogazigi University School of Engineering (BUSoE) has been carried out to determine the perceived strengths and weaknesses of BUSoE.
Keywords: Performance -- Measurement.; Total quality management.; Performance standards.; Universities and colleges -- Accreditation.; Education, Higher -- Directories.; Accreditation (Education).